Unilateral calf atrophy secondary to a de novo mutation of the caveolin-3 gene - Arias Gómez, Manuel; Alberte-Woodwar, Miguel; Arias-Rivas, Susana; Dapena, Dolores; Pintos, Elena; Navarro, Carmen (Muscle & nerve, 2011)
A 23‐year‐old man was evaluated for atrophy of the left calf. He had a myopathic pattern on electromyography. Light microscopy showed dystrophic changes and reduced immunostaining for dysferlin and caveolin‐3. The subsarcolemmal space was enlarged, and abnormal vesicles were visible with electron microscopy. A genetic study showed a heterozygous A45T mutation at exon 2 of the caveolin‐3 gene. Such a mutation has been reported previously with limb‐girdle muscular dystrophy type 1C and rippling muscle disease phenotypes. Muscle Nerve 44: 126–128, 2011.